2010
DOI: 10.3758/cabn.10.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Emotional stimuli modulate readiness for action: A transcranial magnetic stimulation study

Abstract: Emotional stimuli may prime the motor system and facilitate action readiness. Direct evidence for this effect has been shown by recent studies using transcranial magnetic stimulation (TMS). When administered over the primary motor cortex involved in responding, TMS pulses elicit motor-evoked potentials (MEPs) in the represented muscles. The amplitudes of these MEPs reflect the state of corticospinal excitability. Here, we investigated the dynamic effects of induced emotions on action readiness, as reflected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 34 publications
5
85
2
Order By: Relevance
“…The current findings, therefore, demonstrate that although low, moderate, and high tone levels may rely on varying neural circuits (Ehrsson et al, 2001;Spraker et al, 2007), the effect of emotion on these circuits remains fundamentally similar. Emotion leads to an increase in excitability of the motor system, which is reflected in increased force output relative to force production under neutral or benign conditions (Coombes et al, 2008;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;van Loon et al, 2010). Moreover, recent work (i.e., Naugle, Coombes, & Janelle, 2010) has demonstrated that the effect of emotion on sustained force production maybe altered as a function of the relative force levels required on consecutive trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current findings, therefore, demonstrate that although low, moderate, and high tone levels may rely on varying neural circuits (Ehrsson et al, 2001;Spraker et al, 2007), the effect of emotion on these circuits remains fundamentally similar. Emotion leads to an increase in excitability of the motor system, which is reflected in increased force output relative to force production under neutral or benign conditions (Coombes et al, 2008;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;van Loon et al, 2010). Moreover, recent work (i.e., Naugle, Coombes, & Janelle, 2010) has demonstrated that the effect of emotion on sustained force production maybe altered as a function of the relative force levels required on consecutive trials.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009). In conclusion, wexposure to emotional images impacts the accuracy but not variability of a sustained low-level force contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial data indicate that the left amygdala shows greater, or more consistent, activation in response to fear-relevant stimuli than does the right amygdala (see [Baas et al, 2004] and [Zald, 2003], for reviews). The same stimuli that elicit amygdalar responses also activate the corticospinal tract ( [Coelho et al, 2010], [Coombes et al, 2009], [Hajcak et al, 2007], [Schutter et al, 2008] and [van Loon et al, 2010]). The corticospinal tract originates in the primary motor cortex, the fibers cross to the other side of the body at the level of the medulla, and travel down the spinal cord in the lateral corticospinal tract to synapse in the ventral horn in the appropriate spinal cord segment.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have extended this network to include descending white-matter pathways connecting the cortex to the brainstem and spinal cord. Schutter et al (2008; see also [Coombes et al, 2009] and [van Loon et al, 2010]) demonstrated that photographs of faces expressing fear elicited greater excitability in the corticospinal tract than did faces expressing happiness or no emotion (i.e., neutral faces). Similar corticospinal excitability has been detected in response to negative emotional scenes (Coelho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%